Basic research methods an entry to social science research - Guthrie, Gerard (Delhi ; London : SAGE, 2010)
This text offers a comprehensive and rounded view of research as a tool for logical problem-solving. It is built on the philosophical-pragmatic foundation that the value of knowledge and research methodologies lies in their usefulness in engaging with the real world.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Social sciences -- Research; Social sciences -- Research -- Methodology